(untitled) (Lafia Journal of Scientific and Industrial Research, 2025)
This study explored the use of Computer-Aided Design (CAD) software for drafting patterns for training students of Home and Rural Economics in Nasarawa State. Four research questions guided the study which include; what is type of CAD software suitable for pattern drafting? How can CAD instructional materials be developed effectively for students training? What is the importance of integrating CAD into pattern drafting education? What are the challenges of using CAD software in teaching pattern drafting? Research and Development (R&D) design was adopted. Fifty respondents, comprising staff and students of the Department of Home and Rural Economics, College of Agriculture, Science, and Technology Lafia, participated. Structured questionnaire titled “Questionnaire on the Use of CAD for Drafting Patterns as Instructional Material Questionnaire (CADPATTIQ). A Four point rating scale of Strongly Agreed (SA)4, Agreed(A)3, Disagreed(DA)2, and Strongly Disagreed. (SD)1.CAD software such as CorelDraw and Auto CAD were used to develop basic garment patterns including; bodice, skirts, trousers, and sleeves. Data were collected through structured questionnaires and evaluated using mean and Standard Deviation analysis. The results indicated that the use of CAD enhanced precision, creativity, speed, and technological literacy among students. The CAD materials were highly accepted, and respondents agreed that CAD offers significant economic and educational advantages. It is recommended that CAD be integrated into tertiary clothing and textile curricula to better align students with modern industry demands.